Postpurchase Dissonance Observed from Consumer’s Intention as an Innovator, Ability as an Opinion Leaders and Level of Creativity - Eka Danta Jaya Ginting (Jurnal Psikologi, 2010)
This research aims to examine post‐purchase dissonance from the intention of being an innovator, ability as an opinion leader and level of creativity, which were used as indicators by consumers in purchasing some electronic products. In this research the data were collected by using three scales and one assessment tool. They are: Postpurchase Dissonance Scale, Intention as an Innovator Scale, Ability as an Opinion Leader Scale and Figural Creativity Test (Subtest no. 3: Circle). Respondents in this research were those who purchased electronic products with these following conditions: (1). Purchase made no later than one month after the research was conducted; (2). Experienced dissonance after buying the product (with N sample = 120). Data collected in this research were examined by using multiple regression analysis. Based on major hypothesis, it can be concluded that the intention as an innovator, ability as an opinion leader and level of creativity can be used as indicators to predict the arousal of post‐purchase dissonance (where F count = 4.800; p=0.003; R=0.110 & adjusted R square = 0.087). Minor hypothesis also shows that the intention as an innovator can be an indicator to predict the arousal of post‐purchase dissonance (r= ‐0.227; p<0.05). Contrary to that, the other 2 indicators show different result. The ability as an opinion leader has r score = ‐0.228, p>0.05, whereas the level of creativity has r score = ‐0.072; p>0.05.